(untitled) (Journal of Fatima Jinnah Medical University, 2019)
One of the most common cyanotic congenital heart diseases in children is Tetralogy of Fallot (ToF). It occurs in 3 out of every 10,000 live births and accounts for up to one-tenth of all congenital cardiac lesions.2 The patients with cyanotic congenital heart disease are prone to develop cerebral abscess incidence being 4-6%.3 Tetralogy of Fallot is the most common cyanotic congenital heart disease accounting for 13-70% of all brain abscess cases.1,4 Most of them are located in the supratentorial compartment and are most common in 4 to7 years of age.5 The incidence of cerebral abscess in patients with Tetralogy of Fallot is due to the fact that microorganisms in blood, instead of passing through pulmonary circulation and undergoing phagocytosis, passes from right to left heart through the shunt and gains access to cerebral circulation. The prognosis of a cardiogenic abscess is worse than that of other brain abscesses, and mortality rates have ranged from 27.5% to 71%.6 Management options include antibiotics for 6-8 weeks, aspiration under local anesthesia and excision of abscess under general anesthesia. Aspiration of abscess under local anesthesia is the most common because of greater risks associated with general anaesthesia.7